Exile : Guardians of Ga$1 (BHooles #14 - Lasky, Kathryn (New York : Scholastic, 2008)
When the Striga, a mysterious owl from the Middle Kingdom, takes over young King Coryn's mind and institutes a tyrannical new regime, the Band, exiled for their loyalty to Coryn, seek to free him and the kingdom from this threat.
Keywords: Owls -- Fiction; Fantasy; Owls -- Fiction; Fantasy fiction